Revision of Paraloxoblemmus Karny (Orthoptera: Gryllidae; Gryllinae) with a new combination, Paraloxoblemmus longifrons (Chopard 1969), and lectotype designation for Paraloxoblemmus loxoblemmoides (Karny) - Yang, Jeng-Tze (Zootaxa, 2015)
The genus Paraloxoblemmus Karny has not been revised since 1907. In this paper, I present a lectotype designation and photographs of the type species, Paraloxoblemmus loxoblemmoides (Karny). In addition, a new combination Paraloxoblemmus longifrons (Chopard, 1969) is established. This species is transferred from Loxoblemmus Saussure based on the structure of the male genitalia of the holotype. Loxoblemmus longifrons Chopard is relegated as a subjective synonym.